Discovery of halloysite books in altered silicic Quaternary tephras, northern New Zealand. (2nd January 2018) - Cunningham, M.J.; Lowe, D.J.; Wyatt, J.B.; Moon, V.G.; Jock Churchman, G.
Abstract: Hydrated halloysite was discovered in books, a morphology previously associated exclusively with kaolinite. From ∼1.5 to ∼1500 μm in length, the books showed significantly greater mean Fe contents (Fe2 O3 = 5.2 wt.%) than tubes (Fe2 O3 = 3.2 wt.%), and expanded rapidly with formamide. They occurred, along with halloysite tubes, spheroids and plates, in highly porous yet poorly permeable, silt-dominated, Si-rich, pumiceous rhyolitic tephra deposits aged ∼0.93 Ma (Te Puna tephra) and ∼0.27 Ma (Te Ranga tephra) at three sites ∼10–20 m stratigraphically below the modern landsurface in the Tauranga area, eastern North Island, New Zealand. The book-bearing tephras were at or near saturation, but have experienced intermittent partial drying, favouring the proposed changes: solubilized volcanic glass + plagioclase→halloysite spheroids→halloysite tubes→halloysite plates→ halloysite books. Unlike parallel studies elsewhere involving both halloysite and kaolinite, kaolinite has not formed in Tauranga presumably because the low permeability ensures that the sites largely remain locally wet so that the halloysite books are metastable. An implication of the discovery is that some halloysite books in similar settings may have been misidentified previously as kaolinite.